Evaluasi Dampak Program Pengembangan Pertanian Terpadu (Pepadu) pada Kelompok Tani Ternak Sari Buana di Desa Manistutu Kecamatan Melaya Kabupaten Jembrana - JAYA, I GUSTI BAGUS PREMA; PUTRA, I GEDE SETIAWAN ADI; SARJANA, I MADE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.1, Juli 2022, 2022)
Evaluation of the Impact of the Integrated Agricultural Development Program on the Sari Buana Farmers Group in Manistutu Village, Melaya Sub-District, Jembrana Regency.  The integrated agricultural development program is a program developed to combine agricultural and livestock activities in one area in order to increase the utilization and added value of the resulting production without waste. This pattern is one way to preserve the environment rather than the use of chemicals that can adversely affect soil fertility, the quality of the harvest and the freshness of the harvested agricultural products. Therefore, the use of this integrated pattern can maintain the preservation of existing agricultural resources and increase the standard of living of entrepreneurs in agriculture so that it can be managed in a sustainable manner. The purpose of this study is to measure the impact of an integrated agricultural development program looking at three sectors, namely technical impacts, economic impacts and social impacts from the implementation of this integrated agricultural development program. The method used in this research is descriptive qualitative method. This research obtained good results, covering aspects of technical impacts of 86,6%, economic impacts of 97,3%, and social impacts of 93,7%. Hopefully with this farmer group members can maximize their potential both from a technical point of view, especially in artificial assimilation of livestock and also compost management.